1995
DOI: 10.1111/j.1464-410x.1995.tb07843.x
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo activated memory T‐Iymphocytes as adoptive cellular therapy of human renal cell tumour targets with potentiation by cis‐diamminedichloroplatinum(II)

Abstract: These data suggest that: (i) ex vivo activated memory T-cells are the principal component demonstrating significant tumour-specific cytotoxicity of ALT-cells against RCC tumour targets; (ii) CDDP may alter the physical properties of tumour cells rendering them susceptible to immune-mediated attack; (iii) the combination of ALT and CDDP may lead to increased therapeutic efficacy in patients with metastatic RCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…The increase of HLA antigens after incubation of tumor cells with CDDP was also demonstrated measuring the AC-81 adenocarcinoma-associated antigen on gastric cancer cell line KATO-3 [208], increase which resulted in increased susceptibility of the cancer cells to LAK cells and T-lymphocytes cytotoxicity. Similar effects of CDDP had been found by the same group using human soft tissue sarcoma cells [210] or renal cell carcinoma cells [211] as target tumor cells which were modified by CDDP and elicited increased memory T cells responses. Similar effects of CDDP had been found by the same group using human soft tissue sarcoma cells [210] or renal cell carcinoma cells [211] as target tumor cells which were modified by CDDP and elicited increased memory T cells responses.…”
Section: Anticancer Drugssupporting
confidence: 80%
See 2 more Smart Citations
“…The increase of HLA antigens after incubation of tumor cells with CDDP was also demonstrated measuring the AC-81 adenocarcinoma-associated antigen on gastric cancer cell line KATO-3 [208], increase which resulted in increased susceptibility of the cancer cells to LAK cells and T-lymphocytes cytotoxicity. Similar effects of CDDP had been found by the same group using human soft tissue sarcoma cells [210] or renal cell carcinoma cells [211] as target tumor cells which were modified by CDDP and elicited increased memory T cells responses. Similar effects of CDDP had been found by the same group using human soft tissue sarcoma cells [210] or renal cell carcinoma cells [211] as target tumor cells which were modified by CDDP and elicited increased memory T cells responses.…”
Section: Anticancer Drugssupporting
confidence: 80%
“…Indeed at low doses Cyclophosphamide inhibited the growth of murine hepatoma MH129 in immunocompetent but not in immunodepleted mice and the inhibition did not occur in mice given CD4+CD25+ T cells [166]. In this study the interesting observation was made that the administration of low dose Cyclophosphamide was more effective in causing depletion of CD4+CD25+ cells when given after tumor inoculation than when given before tumor inoculation: as the authors stated [166], this finding is of relevance to clinical Phenylalinine mustard + [147,[188][189][190][191] Busulfan + + [148,169,[192][193][194] Nitrosoureas + + [148,[195][196][197][198][199][200][201][202] Cis Platinum + + [170,203,204,205,[206][207][208][209][210][211][212][213][214][215] Difluoromethylornithine + + [280][281][282][283][284][285] trials of chemotherapy and immunotherapy combinations. In this study the interesting observation was made that the administration of low dose Cyclophosphamide was more effective in causing depletion of CD4+CD25+ cells when given after tumor inoculation than when given ...…”
Section: Anticancer Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…We and others have previously confirmed that incubation of human breast, colorectal, and RCC tumor targets with CDDP can either enhance ex vivo lysis of these tumor targets by immune effector cells or allow enhanced ex vivo tumor recognition as measured by interferon-gamma (IFN-y) release [ 19,20,. For ALT-cells, this lysis was dependent on the presence of memory T-cells as depletion of the memory T-cell subset in murine and human TBH significantly reduced lysis of even CDDP-treated tumor targets [3,19,20]. Additionally, there have been reports demonstrating ex vivo lysis of sarcoma tumor targets by antitumor-specific T-cells derived from peripheral blood .…”
Section: Introductionmentioning
confidence: 99%
“…Aside from their direct tumoricidal effects, these agents also possess potent immunomodulatory properties both on the tumor cell itself as well as the adoptively transferred T-cells [9,10, 17,18]. We and others have previously confirmed that incubation of human breast, colorectal, and RCC tumor targets with CDDP can either enhance ex vivo lysis of these tumor targets by immune effector cells or allow enhanced ex vivo tumor recognition as measured by interferon-gamma (IFN-y) release [ 19,20,. For ALT-cells, this lysis was dependent on the presence of memory T-cells as depletion of the memory T-cell subset in murine and human TBH significantly reduced lysis of even CDDP-treated tumor targets [3,19,20].…”
Section: Introductionmentioning
confidence: 99%